DEVELOPMENT OF A QR CODE-BASED E-TICKETING SYSTEM FOR PERFORMANCE EVENTS WITH THE IMPLEMENTATION OF THE SCHMIDT-SAMOA ALGORITHM - Vito Adinugroho, Michel
The development of digital technology has made it easier for people to use tickets with the presence of electronic ticket/e-ticket. E-ticket offer convenience and benefits to overcome the security weaknesses of conventional ticket systems, especially in the ticket validation process. As an effort to overcome these three problems, this final project applies the digital signature concept with the Schmidt-Samoa algorithm to develop a QR Code-based e-ticketing system. This system was developed by encrypting ticket data using the event organizer's private key which ensures the authenticity of the ticket, using public key cryptography algorithm encryption in the database which prevents theft of ticket data, and encrypting the real identity of the ticket buyer to be validated with an identity card which guarantees ticket ownership. The e-ticket system in this final project was developed into two website prototypes, namely the customer website as a ticket purchasing platform and the admin website as a verification platform for validating tickets. The results of the testing phase with various test scenarios show that this system functions well and complies with specifications. Apart from that, the test results also show various key length options that are ideal for use in the system if the user still wants to maintain the efficiency of the ticket verification process, namely 1024 bits for events that require a very fast verification process, and 2048 bits for a 1 second verification process which is still tolerable. By implementing a QR Code-based e-ticketing system that applies the digital signature concept with the Schmidt-Samoa algorithm, tickets are now no longer easy to counterfeit by copying the ticket format, ticket identity is better protected by database encryption, and tickets can now only be used by the ticket owner. This process is carried out well while maintaining the efficiency of the verification process.